Kesalahan Mahasiswa Dalam Menyelesaikan Soal Luas Daerah Bidang Datar Ditinjau Dari Model Analisis Newman - sumargiyani, sumargiyani (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2025)
This research aims to describe the types of student errors in working on flat area area problems using Newman error analysis. This type of research is descriptive qualitative with subjects as many as 25 students of the Mathematics Education Study Program at Ahmad Dahlan University. The research instrument is a written test which is carried out at the Final Semester Examination, and the data is analyzed based on Newman's five stages of error, namely reading, understanding, transformation, process skills, and writing the final result. The research results showed that students made 8% reading errors, 36% comprehension errors, 64% transformation errors, 60% processing skills errors, and 74% writing errors. Factors causing errors include student errors in drawing function graphs, determining the upper and lower limits of integrals, as well as the inability to arrange the solution steps systematically.